Islamic Financial Literacy to Support Islamic Banking Human Resources - Suwandaru, Rachman; Adnan, Asri; Marsuki, Marsuki; Negara Salam, Karta; Nurdin, Maryam (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to determine and analyze the knowledge, beliefs, and skills of Islamic banking human resources in Makassar city at the Well Literate, Sufficient Literate, Less Literate, and Not Literate levels. The research approach uses quantitative research with the data source used is primary data. The research population was Islamic bank employees in Makassar city with a sample of 71 employees. The method used is the structural equation method and measurement model. The analysis methods used are validity and reliability tests, data analysis, descriptive analysis with knowledge (X1), beliefs (X2), and skills (X3) variables. The analytical tool used in this research is Confirmatory Factor Analysis (CFA) used in analyzing indicators that have been grouped based on their latent variables (constructs) with the variables of knowledge (X1), beliefs (X2), and skills (X3) the data is processed using the Amos 20 program. The conclusion that the level of Islamic financial literacy of Islamic bank HR in Makassar city is obtained on the knowledge variable with an average value of 75% at a moderate level or at the Sufficient Literate level. The belief variable from the analysis results shows that the average value of 82% indicates that Islamic banking human resources have a high level of Islamic financial literacy or at the Well Literate level. The skill variable from the analysis results shows that the average value is 80%, this variable also shows a high level of Islamic financial literacy or at the Well Literate level.